A morphological analysis of the waterfront in city centre, Kuala Lumpur - Abdul Latip, Nurul Syala; Heath, Tim; Liew, Mohd Shahir (2009)
The increasing concern for a sustainable development and the significance it should have on future waterfront, places urban design - with its key concern for contextual integration – in a uniquely important position. One of the main factors in contextual integration is the morphological evolution of the place. This paper focuses upon the case study analysing the morphology of Kuala Lumpur waterfront by adopting the method developed by Conzen (1960). Three significant periods of the waterfront development were examined and through this, nineteen waterfront treatments were identified which are suggested vital to be ackowledged for future decision making on the Kuala Lumpur waterfront.